A Pilot Randomized Controlled Trial of a Phone-based Intervention for Smoking Cessation and Relapse Prevention in the Postpartum Period. Issue 3 (May 2018) - Coleman-Cowger, Victoria H.; Mark, Katrina S.; Rosenberry, Zachary R.; Koszowski, Bartosz; Terplan, Mishka
Abstract : Objectives: To pilot-test a Phone-based Postpartum Continuing Care (PPCC) protocol developed from existing evidence-based approaches to address both postpartum smoking relapse among low-income women who quit smoking during pregnancy and postpartum smoking increase among those who had cut down. Methods: One hundred thirty low-income pregnant women who were current or recently quit tobacco smokers were recruited at their first prenatal appointment and randomized to either a Control (standard care) or Experimental (standard care + PPCC) group. An intent-to-treat analysis was conducted on biochemically verified data from 6 in-person interviews during pregnancy and postpartum. Feasibility with regard to recruitment, randomization, assessment, and implementation of PPCC were assessed, along with acceptability among the target population. Results: PPCC was found to be feasible and acceptable to some participants, but not all. There were no significant differences in tobacco products per day at 6 months postpartum between groups; however, effect sizes differed at 6 weeks compared with 6 months postpartum. Similarly, there were no significant differences between groups in cessation rate (24% in each group) and past 90-day tobacco use (59 vs 55 days, for Control and Experimental groups, respectively). Conclusions: The PPCC intervention did not differentially reduce tobacco use postpartum compared with a controlled comparison group, though it was found to be acceptable among a subpopulation of low-income pregnant women and feasible with regard to recruitment, randomization, assessment procedures, and implementation. Further research is needed to identify an intervention that significantly improves smoking relapse rates postpartum. Abstract : Supplemental Digital Content is available in the text